Protein α-amylase inhibitor from withania somnifera and its role in overall quality and nutritional value improvement of potato chips during processing - Kasar, S. S.; Giri, A. P.; Pawar, P. K.; Maheshwari, V. L. (Food and Bioprocess Technology, 2019)
Cold storage and processing increase the reducing sugar level in potato (Solanum tuberosum L.) which is responsible for browning and acrylamide formation that adversely affect sensory and nutrient quality of chips. Effect of α-amylase inhibitor from Withania somnifera (WSAI) treatment on the overall quality improvement of potato chips during processing was studied. WSAI treatment to potato slices at 200 ppm for 30 min was found to reduce browning (60%), residual amylase, and polyphenol oxidase activities (~ 40%) and reduce sugar level by 25%, respectively, over control. Color match analysis indicated an improvement in whiteness and brightness indices and a significant reduction in yellowness index of potato chips. The treatment proved to be superior over blanching and reduction in acrylamide generation during frying was which also observed in chips treated with it. Furthermore, our results were comparable to that of treatment with α-amylase inhibitor of Triticum aestivum and better than synthetic inhibitor, acarbose.
Keywords: Acrylamide; alpha-amylase inhibitor; Browning of potato; Reducing sugars; Sensory and nutrient quality